Body Image dan Kepercayaan Diri: Studi pada Remaja Putri Pengguna Instagram - Diajeng Nisak Rahmawati; Mamang Efendy; Herlan Pratikto (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract Social media, especially Instagram, has a big influence on how teenagers view their bodies, so it has the potential to affect self-confidence. The purpose of this study was to determine the relationship between body image and self-confidence in female adolescents using Instagram social media. The subjects in the study were 105 female adolescents aged 18-21 years who used Instagram. The sampling technique was a purpose sampling with a quantitative research design. Hypothesis testing using the product moment correlation test showed that there was a positive correlation between body image (X) and self-confidence (Y), which means that the hypothesis was accepted. This finding indicate that an improvement in body image is followed by an increase in self-confidence among late adolescent girls who use Instagram, and vice versa. Keywords: Adolescent; Body Image; Self-Confidence Abstrak Media sosial, khususnya instagram memiliki pengaruh besar pada remaja bagaimana memandang tubuh, sehingga berpotensi untuk mempengaruhi kepercayaan diri. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara body image dengan kepercayaan diri remaja akhir putri pengguna media sosial instagram. Subyek pada penelitian adalah remaja perempuan berusia 18 – 21 tahun yang menggunakan instagram berjumlah 105 orang. Teknik pengambilan sampling penelitian ini menggunakan teknik purposive sampling dengan desain penelitian kuantitatif. Pengujian hipotesis menggunakan uji korelasi product moment dan menunjukkan bahwa terdapat korelasi positif antara body image (X) dengan kepercayaan diri (Y), yang mana berarti hipotesis diterima. Hasil penelitian mengindikasikan bahwa peningkatan pada body image diikuti dengan peningkatan kepercayaan diri remaja akhir putri pengguna media sosial istagram, begitu juga sebaliknya. Kata kunci: Body Image; Kepercayaan Diri; Remaja